2011
DOI: 10.1021/nn201136t
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Oriented Ti–Pd Mixed Oxynitride Nanotube Arrays for Enhanced Photoelectrochemical Water Splitting

Abstract: In recent years, considerable efforts have been made to design and discover photoactive nanostructured materials that can be used as anodes in water photoelectrolysis cells. Herein, we report on the growth of a novel photoanode material composed of self-ordered, vertically oriented nanotube arrays of titanium-palladium mixed oxynitride films via anodization of Ti-Pd alloy in an electrolyte solution of formamide containing NH(4)F at room temperature, followed by annealing in an ammonia atmosphere. The nanostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 58 publications
7
65
0
Order By: Relevance
“…The peak interval between Pd 3d 3/2 and 3d 5/2 was 4.7 eV and the intensity ratio of Pd 3d 5/2 to Pd 3d 3/2 was 3/2, which was consistent with theoretical calculation. The presence of Pd 0 indicated that metallic Pd was deposited onto the surface of TNTAs, while the presence of Pd 2+ implied the existence of PdO, possibly from surface oxidation of Pd metal [18,30,34,35]. Besides, the XRD results showed that the diffraction peaks at 2u = 25.5 and 37.9 were assigned to the (1 0 1) and (0 0 4) planes of anatase TiO 2 , respectively (Fig.…”
Section: Fabrication and Photoelectrochemical Performance Of Pd Qds@tmentioning
confidence: 95%
“…The peak interval between Pd 3d 3/2 and 3d 5/2 was 4.7 eV and the intensity ratio of Pd 3d 5/2 to Pd 3d 3/2 was 3/2, which was consistent with theoretical calculation. The presence of Pd 0 indicated that metallic Pd was deposited onto the surface of TNTAs, while the presence of Pd 2+ implied the existence of PdO, possibly from surface oxidation of Pd metal [18,30,34,35]. Besides, the XRD results showed that the diffraction peaks at 2u = 25.5 and 37.9 were assigned to the (1 0 1) and (0 0 4) planes of anatase TiO 2 , respectively (Fig.…”
Section: Fabrication and Photoelectrochemical Performance Of Pd Qds@tmentioning
confidence: 95%
“…Due to the high potential energy of the metal-nitrogen bond compared to the metal-oxygen bond, transition metal oxynitrides [9][10][11][12], are identified as an alternative class of materials that can efficiently be used for solar energy conversion. This difference in bond energy results in narrower band gap energies in oxynitrides compared to their metal oxide counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…This difference in bond energy results in narrower band gap energies in oxynitrides compared to their metal oxide counterparts. In addition, oxynitrides are ideal photoelectrodes for water splitting applications due to their stability in alkaline media [9][10][11][12]. Among all studied oxynitrides, niobium oxynitride (NbON) showed a significant promise as a visible light responsive material with suitable bandedge positions for water splitting [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, relatively low solar utilization percentage of TiO 2 material remains a challenge due to its large band gap (3.2 eV for anatase and 3.0 eV for rutile). Researches have shown that introduction of defects or dopants into the TiO 2 lattice can extend the absorption spectrum of TiO 2 into visible light region [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%